Marketing intelligence. part b : AI, trust, and innovation in the modern business landscape - Sinha, Mudita; Bhandari, Arabinda; Priya, Samant Shant; Kabiraj, Sajal (Emerald Publishing Limited, 2025)
In the rapidly evolving world of business, technology isn't just an asset--it's the driving force behind innovation and success. Marketing Intelligence, Part B: AI, Trust, and Innovation in the Modern Business Landscape brings together cutting-edge insights and strategies from leading experts to explore how AI is transforming industries and redefining the way businesses engage with customers. This book uncovers the intricate relationship between AI-powered technologies and the critical factors of trust and innovation. From harnessing the predictive power of Long Short-Term Memory Network algorithms in dynamic trading environments to leveraging AI for personalized customer experiences in digital lending, Marketing Intelligence, Part B: AI, Trust, and Innovation in the Modern Business Landscape offers a deep dive into the future of business, explores how digital learning can be seamlessly integrated with customer engagement, the importance of trust dynamics in online relationship marketing, and the transformative potential of chatbots and edge computing. With a special focus on sustainable marketing, behavioural finance, and the growing influence of AI in customer interactions, this book provides a holistic view of the modern business landscape. Marketing Intelligence, Part B: AI, Trust, and Innovation in the Modern Business Landscape is an indispensable resource for business leaders, marketers, and technologists who are eager to stay ahead of the curve. It equips readers with the knowledge to harness AI's full potential while fostering trust and driving innovation across industries. Prepare to navigate the complexities of the digital age with strategies that align cutting-edge technology with sustainable and ethical business practices.